ANALISA INTERAKSI SOLENOIDA DAN MEDAN MAGNET UNTUK PEMBUATAN DETEKTOR GEMPA BUMI - Fryan Sopacua; Yono Hadi Pramono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Have been fabricated earthquake detector-based interaction between the solenoid and the permanent magnetic field. The permanent magnet is chosen in such away that the direction of the vector of the magnetic field is proportional to the normal axis in the circle area. The solenoid is designed in such away that it can move inside magnetic field to produced electromotive force ( emf ) induction. The vibration which is caused by the quake will result in a change of a flux inside the solenoid consequently, a change of electric current in the solenoid. The amplitude of an electric current is proportional to the amplitude of the quake. The magnitude of current will be amplified to be readable and will be calibrated in richter scale In the future these sensors will be integrated into the monitoring system potential tsunami earthquake. Keywords: amplitude, electromotive force ( emf ) induction, magnetic field, Richter scale, solenoid.